Ð¢ÐµÑ€Ð°Ð¿ÐµÐ²Ñ‚Ð¸Ñ‡ÐµÑÐºÐ°Ñ Ð³Ð¸Ð¿Ð¾Ñ‚ÐµÑ€Ð¼Ð¸Ñ Ð² Ñ€ÐµÐ°Ð½Ð¸Ð¼Ð°Ñ‚Ð¾Ð»Ð¾Ð³Ð¸Ð¸: Ð¿Ñ€Ð¾ÑˆÐ»Ð¾Ðµ, Ð½Ð°ÑÑ‚Ð¾ÑÑ‰ÐµÐµ, Ð±ÑƒÐ´ÑƒÑ‰ÐµÐµ - Usenko, L. V.; Tsarev, A. V. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2008)
In the article presented the contemporary notions of mechanisms of therapeutic hypothermia and its application for treatment of the critical states.